Gene Regulatory Network Inference and Gene Module Regulating Virulence in Fusarium oxysporum - Cano, Regnier; Lenz, Alexandre Rafael; Galan-Vasquez, Edgardo; Ramirez-Prado, Jorge H.; Perez-Rueda, Ernesto (Frontiers in Microbiology, 2022)
In this work, we inferred the gene regulatory network (GRN) of the fungus Fusarium oxysporum by using the regulatory networks of Aspergillus nidulans FGSC A4, Neurospora crassa OR74A, Saccharomyces cerevisiae S288c, and Fusarium graminearum PH-1 as templates for sequence comparisons. Topological properties to infer the role of transcription factors (TFs) and to identify functional modules were calculated in the GRN. From these analyses, five TFs were identified as hubs, including FOXG_04688 and FOXG_05432, which regulate 2404 and 1864 target genes, respectively. In addition, 16 communities were identified in the GRN, where the largest contains 1923 genes and the smallest contains 227 genes. Finally, the genes associated with virulence were extracted from the GRN and exhaustively analyzed, and we identified a giant module with 10 TFs and 273 target genes, where the most highly connected node corresponds to the transcription factor FOXG_05265, homologous to the putative bZip transcription factor CPTF1 of Claviceps purpurea, which is involved in ergotism disease that affects cereal crops and grasses. The results described in this work can be used for the study of gene regulation in this organism and open the possibility to explore putative genes associated with virulence against their host.